Gastric Adenocarcinoma: A Multimodal Approach - Quadri, Humair S. (Front Surg, 2017)
Despite its declining incidence, gastric cancer (GC) remains a leading cause of cancer-related deaths worldwide. A multimodal approach to GC is critical to ensure optimal patient outcomes. Pretherapy fine resolution contrast-enhanced cross-sectional imaging, endoscopic ultrasound and staging laparoscopy play an important role in patients with newly diagnosed ostensibly operable GC to avoid unnecessary non-therapeutic laparotomies. Currently, margin negative gastrectomy and adequate lymphadenectomy performed at high volume hospitals remain the backbone of GC treatment. Importantly, adequate GC surgery should be integrated in the setting of a multimodal treatment approach. Treatment for advanced GC continues to expand with the emergence of additional lines of systemic and targeted therapies.